PENGARUH PRAPERLAKUAN JUS PISANG AMBON ( Musa paradisiaca L. ) TERHADAP BIOAVAILABILITAS SULFAMEZATIN PADA TIKUS PUTIH JANTAN - Hayati, Farida; Hakim, Arief Rahman; Riptasari, Rhatna Dewi (Jurnal Ilmiah Farmasi, 2004)
The influence of ambon banana’s fruit ( Musa paradisiaca L. ) juice on the bioavailability of sulfamezathin on the rat that aim to know there are interaction result from their consumption together has been studied. The study was using experiment’s animal is white rats Wistar’s spesies that have age around 3-4 months and their weight 200-300 g. This experimental was used completely randomized design with three group’s test, each group’s test is contain seven rats. The first group is pretreatment single dose sulfamezathin (60 mg/kg ww; peroral ), second is sullfamezathin and banana ( 12,6 g/kg ww; peroral ) together and third group is sulfamezathin after one hour dose banana like second group. Respectively blood samples take up from tail vein of rat at 15, 30, 45, 60, 90, 120, 150, 180, 240, 360, 480 and 600 minutes. Consentrations of Sulfamezatin were measured use Bratton Marshall methode with spektrofotometer instrument at 545 mn wavelength. Consentrations of sulfamezathin versus times by software of Stripe used to calculate pharmacokinetics parameters in each group’s test and the value parameters of pharmacokinetics have statistic analysis by ANOVA and if there are difference’s significant ( p < 0,05 ) from calculated value, statistic analysis continued by Tukey test. The results from experimental banana at second and third groups in compare with control at the first group can increased significant ( p < 0,05 ) parameters C maks, t maks, AUC0- .Bioavailability, Sulfamezathin, Ambon banana, Musa paradisiaca L.